THE INFLUENCE OF READER COMMENTS ON STUDENTS' PERCEPTIONS ABOUT CAMPUS NEWS CONTROVERSION THROUGH THE INFLUENCE OF LINE TODAY THROUGH - Sitti Mayasari Pakaya (MEDIALOG: Jurnal Ilmu Komunikasi, 2022)
Technological developments provide significant changes in the field of journalism, especially in the news by the mass media. The online news portal currently provides a comment column feature for news readers to comment on the existing news. This study aims to (1) look at the effect of reader comments on students' perceptions of controversial news about campus through the LINE Today feature, (2) analyze the difference in influence between positive comments and negative comments on students' perceptions of campus controversy news through the LINE Today feature. This study uses a quantitative approach with a questionnaire method to the research population. The sample is students of the Department of Communication, Faculty of Social and Political Sciences, Hasanuddin University who have accounts on the LINE application, totaling 199 people with the total sampling method. Regression analysis technique was used to see the effect of reader comments on student perceptions. To compare the effect of positive and negative reader comments, a comparative analysis technique is used, namely variance. The results showed that (1) There was a significant effect of reader comments on students' perceptions of campus controversy news through the LINE Today feature using both positive and negative stimuli; (2) There is a difference in the effect of positive and negative comments on students' perceptions of campus controversy news through the LINE Today feature.stimuli have a greater influence on student perceptions